Performance analysis of AODV and OLSR routing protocols based on IPv6 mobile ad-hoc networks / Mohamad Hadi Behnia - Behnia, Mohamad Hadi (2010)
obile Ad-hoc Networks (MANETS) are self-configuring and infrastructureless networks which have no dependency on any centralized computer supporting wireless communication in between several mobile nodes. In recent years the number of wireless communication devices had a very fast increase. Moreover, each of these mobile ad-hoc network nodes in order to communicate with each other over the internet, need to be identified by a unique IP address, and the depletion in the number of available pool of unallocated IPv4 internet addresses, has made the IPv6 based Mobile Ad-hoc Networks’ Technology progressively important. Mobile Ad-hoc Network routing protocols such as Ad-hoc On-demand Distance Vector (AODV), Optimized Link State Routing protocol (OLSR), Zone Routing Protocol (ZRP), and Destination Sequenced Distance Vector (DSDV) are standards which control how nodes decide which way to route packets between mobile devices in a MANET. In this research we analyzed the impacts of transition from an IPv4 Mobile Ad-hoc Network to an IPv6 Mobile Ad-hoc Network on the overall performance of the network. We created scenarios in which we simulated mobile ad-hoc networks running both IPv4 and IPv6 MANET, using AODV and OLSR routing protocols. Furthermore, we compared the performance of OLSR and AODV routing protocol in IPv4 and IPv6 networks. We observed in our in our simulation that IPv6 Mobile Adhoc Networks provide better results in the performance of the network. Moreover, AODV routing protocol has better performance results in an IPv6 Mobile Ad-hoc Network in comparison to OLSR routing protocol.